Alcohol and marijuana use in pathways of risk for sexually transmitted infection in white and black adolescent females. Issue 1 (2nd January 2017) - Chung, Tammy; Ye, Feifei; Hipwell, Alison E.; Stepp, Stephanie D.; Miller, Elizabeth; Borrero, Sonya; Hawk, Mary
ABSTRACT: Background : Some types of sexually transmitted infection (STI) have higher prevalence in females than males, and among black, relative to white, females. Identifying mechanisms of STI risk is critical to effective intervention. The authors tested a model in which alcohol and marijuana use serve as mediating factors in the associations between depression and conduct problems with sexual risk behavior (SRB) and STI in adolescent females. Methods : The Pittsburgh Girls Study is a longitudinal observational study of females who have been followed annually to track the course of mental and physical health conditions. The 3 oldest cohorts ( N = 1750; 56.8% black, 43.2% white) provided self-reports of substance use, depression and conduct problems, SRB, and STI at ages 16–18. A path model tested alcohol and marijuana use at age 17 as mechanisms that mediate the associations of depression and conduct problems at age 16 with SRB and STI at age 18. Results : Race was involved in 2 risk pathways. In one pathway, white females reported greater alcohol use, which was associated with greater SRB. In another pathway, black females reported earlier sexual onset, which was associated with subsequent SRB. Public assistance use was independently associated with early sexual onset and STI. SRB, but not substance use, mediated the association of depression and conduct problems with STI. Conclusions : Differences by race in pathways of risk for SRB and STI, involving, for example, alcohol use and early sexual onset, were identified for young white and black females, respectively. Depression and conduct problems may signal risk for SRB and STI in young females, and warrant attention to improve health outcomes.